Polymorphism and association analysis with carcass traits of porcine USF1 gene - WU, HUA-YU; QIAO, MU; PENG, XIAN-WEN; WU, JUN-JING; LIU, GUI-SHENG; SUN, HUA; LI, LIANG-HUA; MEI, SHU-QI (The Indian Journal of Animal Sciences, 2014)
The upstream stimulatory factor 1 (USF1) is a transcription factor controlling expression of several genes involved in lipid and glucose homeostasis. In this study, 2 isoforms of the porcine USF1 gene were detected by reverse transcription polymerase chain reaction (RT-PCR), termed USF1 wild-type (wt) and USF1/CD, both of them contain a helix-loop-helix leucine zipper (HLH-LZ) conserved domain. Tissue distribution analysis showed that the 2 transcripts of porcine USF1 gene were ubiquitously expressed in all tested tissues, except for heart. Moreover, we found that a single nucleotide polymorphism (SNP, C/T) in intron 10 was significantly associated with ratio of lean to fat, dress percentage, average backfat thickness, loin eye width, lean meat percentage, loin eye height and loin eye area. This result suggested that porcine USF1 gene might be a candidate gene of meat production trait.